Rethinking time in preparing for and reflecting on teaching: Pedagogical partnership with student consultants as empowering educational development - Alison Cook-Sather (To Improve the Academy)
How faculty choose—or feel compelled—to spend time on preparing for and reflecting on their teaching is influenced both by capitalist notions of efficiency and productivity and by human, relationship-focused conceptions of growth. The educational development opportunities that faculty are offered at the intersection of these influences can foster self-directed, meaningful, and empowering ways to conceptualize and use time. This article reports on a study that aimed to deepen understanding of how faculty think about, experience, and make choices about time during and after participating in a particular form of educational development: one-on-one pedagogical partnership with liminally positioned student consultants. Anonymous survey responses revealed that, while participating in this form of educational development, faculty experienced pedagogical partnership as a useful/practical way to spend time, as a source of insights into the student perspective on and experience of time, as inspiration to use time to center student learning, and as a worthwhile investment of time to grow as reflective practitioners. Survey responses showed that, after participating in this form of educational development, faculty carried forward new understandings of the importance of spending time outside of class reflecting on teaching, of feeling more confident and capable in planning for teaching, of using time differently in class, and of continuing to invest time in revising their sense of self as a teacher in meaningful learning relationships with students. The article concludes with recommendations for educational developers who wish to support faculty in rethinking time through creating or expanding opportunities to participate in student-faculty pedagogical partnerships.